Pemilihan Makanan Pendamping ASI Pada Batita Dengan Menerapkan Metode TOPSIS - Eka Ridhawati; Leonita Julianti (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2018)
Infants aged six to twenty-four months, starting with complementary feeding of milk (MPASI). MPASI should be sufficient for infants, to meet the nutritional needs of infant growth, with attention to the fulfillment of nutritional needs, nutrition is one factor that must be considered. A mother will prepare food for her baby, taking into account the fulfillment of nutrition, so it will be very efficient in terms of time and energy. Therefore, this study proposes the construction of a system to recommend complementary foods of breast milk. By considering the baby's nutritional needs for optimal infant development, this research uses technique for order preference method by similarity to ideal solution (TOPSIS). Stages performed in this research is data collection, analysis of application methods, implementation, and testing. Determining criteria include brain development, body resistance, optimal physical growth and bone development that takes several alternatives: team rice, vegetable puree, fruit juice, and baby cereal. In this study, the best choice in providing complementary feeding of milk is using an alternative cereal with the yield of 0.619. So from this study concluded that the best alternative is Cereal, with the amount of time to eat according to the baby's age with attention to nutrition to the food ingredients used. Keywords: Complementary Feedi; Baby Nutrition; TOPSIS